Meta-analysis of gene expression profiles of peripheral blood cells in systemic lupus erythematosus - Bae, Sang-Cheol; Lee, Young Ho (Cellular and Molecular Biology, 2018)
Our purpose was to identify differentially expressed (DE) genes and biological processes associated with gene expression changes in systemic lupus erythematosus (SLE). We performed a meta-analysis using the INMEX program (integrative meta-analysis of expression data) on publicly available microarray Genetic Expression Omnibus (GEO) datasets of peripheral blood mononuclear cells (PBMCs) of SLE patients and healthy controls. We performed Gene Ontology (GO) enrichment analysis by using hypergeometric tests. In total, five comparisons (2 B cells, 2 CD4 T cells, and 1 myeloid cell) from two GEO datasets containing 51 cases and 46 controls were included in the meta-analysis. We identified 483 genes consistently differentially expressed in SLE (260 up-regulated and 223 down-regulated). The up-regulated gene with the lowest P-value (P-value = 7.33E-10) was TAP1 (transporter 1, ATP-binding cassette, sub-family B (MDR/TAP)). The up-regulated gene with the largest effect size (ES = 2.7799, P-value = 8.28E-06) was STAT1 (signal transducer and activator of transcription 1, 91 kDa). The down-regulated gene with the lowest P-value (P-value = 2.53E-06) was EIF3F (eukaryotic translation initiation factor 3, subunit F), and the down-regulated gene with the largest ES (ES = âˆ’1.8543, P-value = 8.56E-06) was FBL (fibrillarin). The most significant enrichment among 317 GO categories was the type I interferon (IFN)-mediated signaling pathway with P = 1.93E-20. Other significant GO categories included cellular response to type I IFN (P = 1.93E-20) and response to type I IFN (P = 2.86E-20). Our meta-analysis demonstrates that up-regulated genes mediate IFN-regulated and cytokine-mediate signaling pathways, innate immune response, and antigen processing and presentation. These results provide insights into molecular mechanisms associated to the pathophysiology of SLE.